Image encryption algorithm based on a new one-dimensional chaotic map’s generator - Htiti, Mohamed; Akharraz, Ismail; Ahaitouf, Abdelaziz (Institute of Advanced Engineering and Science, 2025)
Encryption plays a crucial role in protecting sensitive data, including communications, financial transactions, and personal information, from cyber threats. One significant area of encryption is image encryption, which ensures the privacy of visual content, such as in secure image transmission, cloud storage, and medical image processing. Recent advancements in image encryption leverage chaotic maps based on chaos theory, generating unpredictable patterns ideal for securing images. This paper presents a novel chaotic map generator that enhances the dynamics of existing chaotic maps. Based on this generator, we propose a new encryption scheme that operates on the entire input image, obscuring the relationship between the original and encrypted images while spreading pixel changes across the entire encrypted image in one step. The scheme also produces an encrypted image of a different size, making it more efficient and resilient to attacks. While some steps of the proposed system are symmetric, others are asymmetric, ensuring a higher level of security. Based on the obtained results, this approach significantly enhances both security and performance in image encryption.